Designing new interface for non-cultural influence tourism mobile application - Foo, Jamie Xuet Phing (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The mobile tourism application is gaining its popularity in the tourism industry. Internationalization is also getting more important as it design to cater for users of all nations and cultures. Designing a usable yet universal interface mobile application for the tourism industry is of the essential as many users are downloading travel related applications into their mobile devices. The aim of this study to design an international interface which was investigated on the users’ preference for the selected design elements based on the existing design interface that was culturally influenced. The focus design elements of this project will be on colour, layout and navigation. The result from data collection process will be analysed using the Friedman Test which gives the mean rank which were first collected using the Semantic Differential scale questionnaire. The analysed data suggest on the preference of users on the three design elements. A prototype is developed based on the proposed guidelines.